Strengthening Indigenous Welfare through the Role of Local Government Initiatives in Protecting Traditional Knowledge - Ida Hanifah; Koto, Ismail; Faisal, Faisal; Zainuddin, Zainuddin; Imsirovic, Mirela (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
The communal culture of traditional societies fundamentally contrasts with the individualistic framework of intellectual property rights (IPR). Indigenous communities prioritize collective interests without negating individual rights. This study aims to examine and analyze the optimization of traditional knowledge protection as an effort to improve the welfare of communal societies. The research employs a normative juridical method by reviewing statutory regulations and related legal instruments. The findings reveal that communal intellectual property is recognized under both international and national legal frameworks. National regulations require each region to conduct an inventory of community intellectual property; however, public awareness of its importance remains limited. Therefore, renewed strategies are needed to ensure that communities fully understand the economic, social, and cultural value of their traditional knowledge. Local governments play a crucial role in disseminating information and implementing inventory programs through regional regulations. Furthermore, the development of traditional knowledge–based products can be advanced to the industrialization stage through Micro, Small, and Medium Enterprises (MSMEs), thereby supporting the welfare of indigenous peoples. The ideal model of local government intellectual property protection is to guarantee community ownership rights while ensuring a fair profit-sharing mechanism with third parties.